2004
DOI: 10.1111/j.1365-2044.2004.03900.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of xenon and nitrous oxide in patients during fentanyl‐midazolam anaesthesia*

Abstract: SummaryXenon anaesthesia appears to have minimal haemodynamic effects. The purpose of this randomised prospective study was to compare the cardiovascular effects of xenon and nitrous oxide in patients with known ischaemic heart disease. In 20 patients who were due to undergo coronary artery bypass graft surgery, 30 min following induction of anaesthesia with fentanyl 30 lg.kg )1 and midazolam 0.1 mg.kg )1 but prior to the start of surgery, xenon or nitrous oxide 60% was administered for 15 min. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
2
25
0
2
Order By: Relevance
“…Xe 60% has been associated with better left ventricular performance [26] and systolic function [27] in patients with moderate cardiovascular risk [26] and ischaemic heart disease [27], respectively. Other possible mechanisms for maintaining stable MABP may be due to the preservation of the systemic vascular resistance and myocardial contractility following inhalation of Xe 50-70% in pigs [25], Xe 63% in dogs [28], and Xe 15-53% in humans who underwent coronary artery bypass grafts [29].…”
Section: Discussionmentioning
confidence: 99%
“…Xe 60% has been associated with better left ventricular performance [26] and systolic function [27] in patients with moderate cardiovascular risk [26] and ischaemic heart disease [27], respectively. Other possible mechanisms for maintaining stable MABP may be due to the preservation of the systemic vascular resistance and myocardial contractility following inhalation of Xe 50-70% in pigs [25], Xe 63% in dogs [28], and Xe 15-53% in humans who underwent coronary artery bypass grafts [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of these findings on morbidity and mortality in high risk surgical patients is unknown. To date, only two investigations have studied the effects of xenon administration in high risk surgical patients [2,26]. In a study comparing the effects of xenon-and propofolbased sedation regimens following coronary artery bypass grafting (CABG), xenon performed comparably to propofol with respect to cardiovascular stability [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Goto and coworkers compared the effect of xenon and nitrous oxide on left ventricular performance and haemodynamics in patients prior to CABG and found that contractility was preserved with xenon (as assessed with FAC and left ventricular stroke work index), whereas after nitrous oxide administration, mean arterial blood pressure and contractility deteriorated [2]. However, nitrous oxide administration in patients with a limited cardiovascular reserve is not common, and therefore xenon should be compared with total intravenous or balanced anaesthesia regimens [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 142 surgical patients xenon anesthesia was well tolerated except for more nausea and vomiting compared to those randomized to propofol (30). Several other studies in surgical patients reported xenon was well tolerated as an anesthetic (31)(32)(33)(34). In a pilot study of critical care sedation for 8 hours, 21 patients randomized to either propofol or inhaled xenon (9-62 %) had comparable sedation.…”
Section: Introductionmentioning
confidence: 91%